Competing in Product and Service: A Product Life-Cycle Model - Cohen, Morris A.; Whang, Seungjin (Management Science, 1997)
In this paper we develop a product life-cycle model that studies a set of strategic choices facing manufacturers as they design the joint product/service bundle for a product which may require maintenance and repair support after its sale. The choice parameters of interest include the product price, the quality of after-sales service and the price to be charged for the after-sales service. We adopt a competitive, game-theoretic (as opposed to single-firm optimization) framework, where there is competition for the provision of after-sales service between the manufacturer and an independent service operator. The product price and the service quality/price are characterized by an equilibrium to a sequential game. The resulting outcome is applied to support the valuation of alternative product designs in explicit consideration of the tradeoff between profit from product sale and from the provision of after-sales service. The model can also be used to evaluate the asset value of a firm's customer base.